The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1063/1.2963708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of near-surface modification of polystyrene: Bombardment with Ar+ and Ar+/radical chemistries

Abstract: Molecular dynamics (MD) simulations have been carried out to examine the effects of Ar+, Ar+/H, and Ar+/F bombardment of a model polystyrene (PS) surface. For bombardment with 100 eV Ar+ only, the simulations show the formation of a heavily cross-linked dehydrogenated damaged layer in the near-surface region after some initial fluence, consistent with plasma and beam system experimental results. The 1–2 nm thick amorphous carbon-rich modified layer has a much lower sputter yield compared to that of the virgin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 48 publications
7
33
0
Order By: Relevance
“…While the dependence of surface roughness on ion energy is opposite for PS and PMMA etched in Ar/O 2 , the surface roughness features are similar in size and form [12] suggesting that the same roughening mechanism is involved. The role of cross-linking is further explored through the use of alternate etch gas mixtures that are expected to suppress cross-linking [19]. Surface roughness of Ar/H 2 and Ar/F 2 etched PS and PMMA samples with four substrate bias voltages: −30 V to −150 V (ion energy: 45 eV to 165 eV) are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While the dependence of surface roughness on ion energy is opposite for PS and PMMA etched in Ar/O 2 , the surface roughness features are similar in size and form [12] suggesting that the same roughening mechanism is involved. The role of cross-linking is further explored through the use of alternate etch gas mixtures that are expected to suppress cross-linking [19]. Surface roughness of Ar/H 2 and Ar/F 2 etched PS and PMMA samples with four substrate bias voltages: −30 V to −150 V (ion energy: 45 eV to 165 eV) are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of PS, surface cross-linking is prevalent, while in PMMA, chain scissioning and depolymerization dominate [13,14,16]. While chemical structures such as the aromatic ring in PS and the methyl ester group in PMMA are commonly believed to play important roles in etching behaviors such as etch rate, cross-linking and chain scission, most studies reporting a correlation between chemical structures and etch behaviors of polymers are based on indirect observations, including change in molecular weight [16], etch rate [13,19], interface adhesion [14,16] or diffusion coefficient [20]. Details of the mechanisms involved have yet to be elucidated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…poly͑methyl methacrylate͒ ͑PMMA͒, 8 193 and 248 nm photoresists 5,6,9,10 ͔ and has been described as a thin, highly crosslinked and graphitized layer. [4][5][6][11][12][13][14][15][16] We have previously shown that under energetic Ar + ion bombardment during plasma etching, a dense, amorphous carbonlike modified layer is formed at the surface of a wide range of polymers ͓polystyrene ͑PS͒, poly͑␣-methylstyrene͒, poly͑4-methylstyrene͒, PMMA, poly͑hydroxyadamantyl acrylate͒, and poly͑hydroxyadaman-tyl methacrylate͔͒ with a thickness of a few nanometers. 17 This modified layer forms within the first few seconds of plasma exposure ͑corresponding to an ion fluence ϳ4 ϫ 10 16 cm −2 ͒, concurrent with a period of rapid surface roughening.…”
Section: Introductionmentioning
confidence: 99%